1995
DOI: 10.1042/bj3080045
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the glycolipid anchor of lipophosphoglycan and the structurally related glycoinositolphospholipids from Leishmania major

Abstract: The major macromolecule on the surface of the protozoan parasite Leishmania major is a lipophosphoglycan (LPG) which contains a glycosylphosphatidylinositol glycolipid anchor. This parasite also synthesizes a complex family of abundant low-molecular-mass glycoinositolphospholipids (GIPLs) which are structurally related to the LPG anchor. In this study, L. major promastigotes were metabolically labelled with [3H]GlcN, and the kinetics of incorporation into free glycolipids and the LPG anchor followed to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…1). The decrease in the rate of synthesis of LPG was matched by a decrease in the size of the LPG steady-state pool, consistent with previous studies showing that LPG is rapidly shed from the plasma membrane (37). However, the steady-state pools of the GIPLs either remained unchanged in the promastigote stages or increased 3-fold in LA.…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…1). The decrease in the rate of synthesis of LPG was matched by a decrease in the size of the LPG steady-state pool, consistent with previous studies showing that LPG is rapidly shed from the plasma membrane (37). However, the steady-state pools of the GIPLs either remained unchanged in the promastigote stages or increased 3-fold in LA.…”
Section: Figsupporting
confidence: 78%
“…However, the steady-state pools of the GIPLs either remained unchanged in the promastigote stages or increased 3-fold in LA. The major GIPL species contain two fatty chains, rather than the single alkyl chain in the LPG anchor, which may increase their stability in the plasma membrane (37). As these glycolipids would still be diluted during cell division, their unchanging pool size indicates that the growth rate of amastigotes in mature lesions must be comparatively slow.…”
Section: Figmentioning
confidence: 99%
“…h-'/cell. This figure, although substantial, is only about 7% of the activity that would be required by L. major to turn over approximately half of its 3 -5 X lo6 copies of procyclic promastigote lipophosphoglycan (containing an average of 16 Man-P residues [6]) in an hour [29]. A similarly low yield has also been reported for the pgalactosyltransferase activity that modifies the phosphosaccharide repeats of L. mujor lipophosphoglycan [23].…”
Section: Discussionmentioning
confidence: 89%
“…The presence of lipid on a small proportion of CM-AGPs, however, suggests that AGPs with GPI lipid anchors are amphipathic enough to sometimes release from the plasma membrane by stochastic biophysical partitioning, as reported for the GPI-anchored lipophosphoglycan of L. major (35).…”
Section: Discussionmentioning
confidence: 94%
“…A solution to this dilemma was suggested by the literature on the protozoan parasite Leishmania major, the plasma membrane of which contains both a lipophosphoglycan with GPI lipid anchor and a structurally related glycoinositolphospholipid. Proudfoot et al (35) found that appreciable shedding of lipophosphoglycan from the plasma membrane occurred as a stochastic biophysical event in which the highly polar polysaccharide portion of the lipophosphoglycan occasionally pulled the lipid anchor out of the membrane into the aqueous medium. No shedding of glycoinositolphospholipid from the membrane occurred, however, because its oligosaccharide head group, although also polar, was too small to pull the lipid anchor out of the membrane.…”
Section: Resultsmentioning
confidence: 99%